The Learning Continuum: A Model for Sustained Participation with Hard-to-Serve Clients - Elizabeth B. Bolton (EDIS)
This report, The Learning Continuum: A Model for Sustained Participation with Hard-to-Serve Clients, is part of the UF/IFAS Welfare-to-Work Initiative (Grant #A6218) funded by the Florida Agency for Workforce Innovation (formerly Florida Department of Labor and Employment Security). The Principal Investigator is Elizabeth B. Bolton, Professor of Community Development, Department of Family, Youth and Community Sciences.